Battery
By using copper foil containing silicon elements in the negative electrode sheet of the lithium-ion battery and adding ether nitrile compound to the electrolyte to form a passivation film, the copper foil corrosion caused by HF in the electrolyte is solved, and the safety performance of the battery is improved.
Patent Information
- Application Number
- CN202411923129.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-02-28
AI Technical Summary
The hydrolysis of lithium hexafluorophosphate in the electrolyte of existing lithium-ion batteries produces HF, causing corrosion of copper foil and forming Cu dendrites, increasing the risk of battery short circuit and fire explosion, and reducing safety performance.
The copper foil containing silicon elements is added to the negative electrode sheet of the battery, and an ether nitrile compound is added to the electrolyte solution. The silicon element catalyzed the ether nitrile compound to form a passivation film on the surface of the copper foil to prevent corrosion of acidic substances.
Effectively inhibit the corrosion of copper foil, prevent the formation of Cu dendrites, reduce the risk of battery short circuit and fire explosion, and improve the safety performance of the battery.
Smart Images

Figure BDA0005208534450000011 
Figure BDA0005208534450000021 
Figure BDA0005208534450000031
Abstract
Description
Technical Field
[0001] The invention relates to a battery and belongs to the field of lithium ion batteries. Background Art
[0002] Lithium-ion batteries are widely used in laptops, mobile phones, digital products and other fields due to their advantages such as high energy density, high safety performance, long cycle life and environmental friendliness.
[0003] The electrolyte of the commonly used lithium-ion battery is generally composed of carbonate solvent and lithium hexafluorophosphate, but the electrolyte has a defect, that is, lithium hexafluorophosphate will hydrolyze to produce HF. The HF produced in the electrolyte can corrode the current collector of the battery, especially the copper foil (aluminum foil can form a dense passivation film in the air). After the copper foil is corroded, Cu ions will be dissolved. The dissolved Cu ions will form Cu dendrites during the charge and discharge process. The Cu dendrites may pierce the copper foil, causing a short circuit between the positive and negative electrodes, and ultimately causing the battery to catch fire and explode, reducing the safety performance of the battery.
[0004] Therefore, those skilled in the art are in urgent need of providing a technology that can inhibit copper foil corrosion, thereby improving the safety performance of the battery. Summary of the invention
[0005] The present invention provides a battery in which the corrosion of copper foil can be suppressed, thereby improving the safety performance of the battery.
[0006] The present invention provides a battery, comprising a positive electrode sheet, a negative electrode sheet and an electrolyte, wherein the negative electrode sheet comprises a negative electrode current collector, the negative electrode current collector comprises a copper foil, and the copper foil comprises silicon element;
[0007] The electrolyte includes an ether nitrile compound.
[0008] The battery as described above, wherein the ether nitrile compound comprises a compound represented by Formula 1:
[0009]
[0010] Wherein, R is selected from substituted or unsubstituted C1-C30 alkyl, and the substituent of R includes C1-C10 alkoxy, cyano, -O-(CH2) m -At least one of CN; n is selected from an integer between 0 and 5, and m is selected from an integer between 1 and 8;
[0011] Preferably, R is selected from substituted or unsubstituted C1-C20 alkyl, and the substituents of R include C1-C5 alkoxy, cyano, -O-(CH2) m -At least one of CN; n is selected from 0, 1, 2, and m is selected from an integer from 1-5.
[0012] The battery as described above, wherein the compound represented by Formula 1 includes at least one of the compounds represented by Formula 2 to Formula 20:
[0013]
[0014]
[0015] In the battery as described above, the mass content of the silicon element in the copper foil is 700-2000 ppm; and / or the mass content of the compound represented by Formula 1 in the electrolyte is 1000-50000 ppm.
[0016] The battery as described above, wherein the positive electrode sheet in the battery comprises a positive electrode active material layer, and the thickness of the positive electrode active material layer is 0.4-1000 μm;
[0017] Preferably, the thickness of the positive electrode active material layer is 20-130 μm.
[0018] The battery as described above, wherein the roughness of the copper foil is ≤1 μm.
[0019] The battery as described above, wherein the electrolyte further comprises a compound represented by Formula 21:
[0020]
[0021] In the battery as described above, the mass percentage F of the compound represented by Formula 21 in the electrolyte satisfies: 0.01%≤F≤0.05%.
[0022] In the battery as described above, the negative electrode comprises a negative electrode active material layer, and the thickness of the negative electrode active material layer is 30-180 μm.
[0023] The battery as described above, wherein the positive electrode comprises a positive electrode active material, the positive electrode active material comprises a transition metal lithium oxide, and the chemical formula of the transition metal lithium oxide is Li 1+x Ni y Co z M (1-y-z) O2, wherein -0.1≤x≤1, 0≤y≤1, 0≤z≤1, and 0≤y+z≤1, and M includes at least one of Mg, Zn, Ga, Ba, Al, Fe, Cr, Sn, V, Mn, Sc, Ti, Nb, Mo, and Zr;
[0024] And / or, the negative electrode active material includes a silicon-based negative electrode material, and the silicon-based negative electrode material includes at least one of a silicon-oxygen negative electrode material and a silicon-carbon negative electrode material.
[0025] The copper foil of the present invention contains silicon element and the electrolyte contains ether nitrile compound. The silicon element in the copper foil can catalyze the ether nitrile compound to form a passivation film on the surface of the copper foil, thereby preventing acidic substances such as PF5, POF3, HF generated in the electrolyte from corroding the copper foil, avoiding the generation of copper dendrites, and preventing copper dendrites from piercing the copper foil and causing a battery short circuit, thereby improving the safety performance of the battery. DETAILED DESCRIPTION
[0026] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0027] The invention provides a battery, which comprises a positive electrode sheet, a negative electrode sheet and an electrolyte, wherein the negative electrode sheet comprises a negative electrode current collector, the negative electrode current collector comprises a copper foil, and the copper foil comprises silicon element; and the electrolyte comprises an ether nitrile compound.
[0028] The ether nitrile compound of the present invention refers to a compound containing an ether group and a cyano group.
[0029] According to the solution provided by the present invention, the copper foil and the electrolyte are applied to a battery, and the battery has excellent safety performance. The inventor has analyzed this principle and believes that the reason may be that the copper foil of the present invention contains silicon and the electrolyte contains ether nitrile compounds. The silicon element in the copper foil can catalyze the ether nitrile compounds to form a passivation film on the surface of the copper foil, thereby preventing acidic substances such as PF5, POF3, and HF in the electrolyte from corroding the copper foil, avoiding the generation of copper dendrites, and preventing copper dendrites from piercing the copper foil and causing a battery short circuit, thereby improving the safety performance of the battery.
[0030] In a specific embodiment, the ether nitrile compound includes a compound shown in Formula 1:
[0031]
[0032] Wherein, R is selected from substituted or unsubstituted C1-C30 alkyl, and the substituent of R includes C1-C10 alkoxy, cyano, -O-(CH2) m -At least one of CN; n is selected from an integer between 0 and 5, and m is selected from an integer between 1 and 8;
[0033] Preferably, R is selected from substituted or unsubstituted C1-C20 alkyl, and the substituents of R include C1-C5 alkoxy, cyano, -O-(CH2) m-At least one of CN; n is selected from 0, 1, 2, and m is selected from an integer from 1-5.
[0034] The electrolyte of the present invention comprises a compound as shown in Formula 1, wherein R is selected from a substituted or unsubstituted C1-C30 alkyl group, and the substituent of R comprises a C1-C10 alkoxy group, a cyano group, -O-(CH2) m -CN; n is an integer selected from 0 to 5, and m is an integer selected from 1 to 8. The substituted or unsubstituted C1-C30 alkyl group of the present invention refers to a substituted or unsubstituted chain alkyl group with 1 to 30 carbon atoms or a substituted or unsubstituted cycloalkyl group with 3 to 30 carbon atoms; C1-C10 alkoxy group refers to an alkoxy group with 1 to 10 carbon atoms; -O-(CH2) m -CN, m is selected from an integer of 1-8 and refers to -OCH2CN, -OCH2CH2CN, -O-(CH2)3CN, -O-(CH2)4CN, -O-(CH2)5CN, -O-(CH2)6CN, -O-(CH2)7CN or -O-(CH2)8CN. When a substituent is specified as a group with a specific carbon number, all geometric isomers with that carbon number are included. For example, R can be selected from -CH3, -CH2CH3, -CH2CH2CH3, -CH2CH2CN, -CH2CH2CH2CN, -CH2-O-CH3, -CH2-O-(CH2)2CN, -CH2-O-(CH2)3CN, etc.
[0035] When the ether nitrile compound is the compound of formula 1, the silicon element can better catalyze the compound of formula 1, making the passivation film formed by the compound of formula 1 denser, thus avoiding corrosion of the copper foil to a greater extent, thereby better improving the safety performance of the battery.
[0036] In a specific embodiment, the compound represented by Formula 1 includes at least one of the compounds represented by Formula 2 to Formula 20:
[0037]
[0038]
[0039] When the compound of formula 1 is selected from the above compounds, the compound of formula 1 can form a denser passivation film on the surface of the copper foil, thereby preventing corrosion of the copper foil to a greater extent and reducing the formation of copper dendrites, thereby further improving the safety performance of the battery.
[0040] In a specific embodiment, the mass content of silicon in the copper foil is 700-2000ppm, for example, 700ppm, 800ppm, 900ppm, 1000ppm, 1100ppm, 1200ppm, 1300ppm, 1400ppm, 1500ppm, 1600ppm, 1700ppm, 1800ppm, 1900ppm or 2000ppm, etc. When the mass content of silicon in the copper foil is within the above range, the strength and ductility of the copper foil are high, which is conducive to the coating of the negative electrode active layer and improves the stability of the battery. The passivation layer on the surface of the copper foil is thick enough to improve the safety performance of the battery. At the same time, the use of the compound of formula 1 can be reduced, and the compound of formula 1 can be avoided to form a thick protective layer on the positive and negative electrodes and to avoid excessive thickness of the passivation layer, so as to avoid an increase in the internal resistance of the battery, thereby ensuring the cycle performance of the battery.
[0041] Specifically, the copper foil of the present invention is subjected to an ICP test to obtain the mass content of silicon in the copper foil.
[0042] In a specific embodiment, the mass content of the compound represented by Formula 1 in the electrolyte is 1000-50000ppm, for example, 1000ppm, 5000ppm, 10000ppm, 15000ppm, 20000ppm, 25000ppm, 30000ppm, 35000ppm, 40000ppm, 45000ppm or 50000ppm, etc. When the mass content of the compound of Formula 1 in the electrolyte is within the above range, the compound of Formula 1 can form a sufficiently thick passivation layer on the surface of the copper foil to avoid corrosion of the copper foil, thereby improving the safety performance of the battery to a greater extent, and the compound of Formula 1 can form a protective layer of suitable thickness on the surface of the positive electrode and the negative electrode to avoid an increase in the internal resistance of the battery, thereby improving the cycle performance of the battery.
[0043] In a specific embodiment, the positive electrode sheet in the battery includes a positive electrode active material layer, and the thickness of the positive electrode active material layer is 20-130 μm, for example, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 110 μm, 120 μm or 130 μm.
[0044] When the single-sided thickness of the positive electrode active material layer is within the above range, it means that the compound of Formula 1 can form a dense protective film with appropriate thickness on the surface of the positive electrode active material layer, so that the protective film can fully protect the components in the positive electrode active material layer, and avoid the components in the positive electrode active material layer from reacting with the components in the electrolyte, thereby improving the high temperature performance, safety performance and low temperature performance of the battery.
[0045] In a specific embodiment, the roughness of the copper foil is ≤1 μm, for example, 0.1 μm, 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm or 1 μm. When the roughness of the copper foil is within the above range, the contact angle between the copper foil and the electrolyte can be increased, and the wettability of the electrolyte to the copper foil can be reduced, thereby reducing the corrosion of the electrolyte to the copper foil and improving the safety performance of the battery.
[0046] Specifically, the roughness of the copper foil can be obtained by performing the following test on the copper foil: take a sample with a side length of 50±0.2mm and a thickness equal to the thickness of the copper foil at the center and both sides in the width direction of the copper foil, for a total of 3 samples, and then use a surface roughness measuring instrument with a probe to measure one data in the longitudinal and transverse directions of each sample, for a total of 6 data for the 3 samples, and take the arithmetic average as the roughness of the copper foil.
[0047] In a specific embodiment, the copper foil is prepared by a process comprising the following steps:
[0048] The copper foil is subjected to ultrasonic impact treatment using a steel ball with a diameter of 1 mm to obtain the copper foil;
[0049] The ultrasonic impact treatment has an ultrasonic frequency of 20 Hz and a duration of 10 s.
[0050] Specifically, a steel ball with a diameter of 1 mm is placed in an ultrasonic impact chamber, and the copper foil is fixed on the top of the ultrasonic impact chamber to perform ultrasonic impact treatment with an ultrasonic frequency of 20 to 100 Hz and a time of 10 to 100 s to obtain the copper foil.
[0051] The present invention does not limit the size of the copper foil, and the size can be selected according to actual needs. For example, a copper foil with a thickness of 6 mm can be selected.
[0052] The present invention can perform microcrystallization treatment on the surface of copper foil through ultrasonic impact treatment, so that steel balls form tiny three-dimensional structures on the surface of copper foil, so that the roughness of copper foil can be within the above range, thereby increasing the contact angle between copper foil and electrolyte and improving the safety performance of battery.
[0053] In a specific embodiment, the electrolyte further includes a compound represented by formula 21:
[0054]
[0055] When the compound of formula 21 is added to the electrolyte, the compound of formula 21 can act synergistically with the compound of formula 1 to form a denser and more stable passivation layer on the surface of the copper foil, thereby suppressing the reaction between the copper foil and the electrolyte to a greater extent, thereby improving the safety performance of the battery. In addition, the compound of formula 21 can act synergistically with the compound of formula 1 to form a protective layer on the surface of the negative electrode, thereby avoiding side reactions between the negative electrode and the electrolyte and improving the cycle performance of the battery.
[0056] In a specific embodiment, the mass percentage content F of the compound represented by Formula 21 in the electrolyte satisfies: 0.01%≤F≤0.05%, for example, F is 0.01%, 0.015%, 0.02%, 0.025%, 0.03%, 0.035%, 0.04%, 0.045% or 0.05%, etc. When the mass percentage content of the compound of Formula 21 is within the above range, the compound of Formula 21 and the compound of Formula 1 can synergistically form a passivation film with suitable thickness and higher density, so that the stability of the copper foil is higher, and the safety performance of the battery is further improved. At the same time, the compound of Formula 21 can synergistically form a protective film on the surface of the negative electrode with the compound of Formula 1. The protective film has high density and reasonable thickness, can protect the negative electrode and avoid the increase of the internal resistance of the battery, so as to make the cycle performance of the battery better.
[0057] In a specific embodiment, the battery further includes a negative electrode active material layer, and the thickness of the negative electrode active material layer is 30-180 μm, for example, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 110 μm, 120 μm, 130 μm, 140 μm, 150 μm, 160 μm, 170 μm or 180 μm. When the single-sided thickness of the negative electrode active layer is within the above range, it indicates that the negative electrode protective film synergistically generated by the compound of Formula 1 and the compound of Formula 21 can fully protect the negative electrode active material layer, avoid side reactions between the components of the negative electrode active material layer and the electrolyte, and make the battery cycle performance better.
[0058] In a specific embodiment, the electrolyte further includes a lithium salt, and the lithium salt includes at least one of lithium perchlorate, lithium hexafluorophosphate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium tetrafluorooxalatophosphate, lithium bis(fluorosulfonylimide), lithium bis(trifluoromethylsulfonylimide), lithium difluorobis(oxalatophosphate), lithium tetrafluoroborate, lithium bis(oxalatoborate), lithium hexafluoroantimonate, lithium hexafluoroarsenate, 4,5-dicyano-2-trifluoromethyl-imidazole lithium, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(pentafluoroethylsulfonyl)imide, tris(trifluoromethylsulfonyl)methyl lithium or lithium bis(trifluoromethylsulfonyl)imide; the mass percentage of the lithium salt in the electrolyte is 11-18%, for example, 11%, 12%, 13%, 14%, 15%, 16%, 17% or 18%, etc. When the lithium salt is selected from the above-mentioned lithium-containing compounds, the lithium salt can be completely dissolved in the organic solvent to form a highly stable electrolyte, so that lithium ions can be quickly dissociated and transferred in the electrolyte, thereby improving the conductivity of the electrolyte and thus improving the cycle performance of the battery.
[0059] In a specific embodiment, the electrolyte further includes an organic solvent, and the organic solvent includes carbonate and / or carboxylate; the carbonate includes at least one of the following fluorinated or unsubstituted solvents: ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate; the carboxylate includes at least one of the following fluorinated or unsubstituted solvents: propyl acetate, n-butyl acetate, isobutyl acetate, n-amyl acetate, isoamyl acetate, propyl propionate, ethyl propionate, methyl butyrate, ethyl butyrate. When the above organic solvents are selected, the organic solvent can completely dissolve the lithium salt to achieve an electrolyte with high conductivity and strong stability, which is beneficial to the improvement of the electrochemical performance of the lithium ion battery.
[0060] The present invention does not limit the preparation method of the electrolyte. In a specific implementation, it is sufficient to mix the lithium salt, the organic solvent, and the compound of formula 1 in a prescribed ratio.
[0061] Furthermore, when the electrolyte further includes the compound of formula 21, the lithium salt, the organic solvent, the compound of formula 1, and the compound of formula 21 are mixed in a prescribed ratio.
[0062] In a specific embodiment, the positive electrode active material layer includes: 80-99.8% positive electrode active material, 0.1-10% conductive agent, and 0.1-10% binder. When the content of each component in the positive electrode active material layer is within the above range, the conductivity of the positive electrode active material layer can be further improved, so that the positive electrode active material layer can be better attached to the positive electrode current collector, thereby improving the electron and ion transmission performance, making the battery present a higher cycle performance, and can avoid the shedding of the positive electrode active material layer, and improve the safety performance of the battery. Preferably, the positive electrode active material layer includes: 90-99.6% positive electrode active material, 0.2-5% conductive agent, and 0.2-5% binder.
[0063] The present invention does not limit the selection of the conductive agent and the binder in the positive electrode active material layer. For example, the conductive agent and the binder may be conventional materials in the art, and may be specifically configured as required.
[0064] The present invention does not limit the selection of the positive electrode current collector, and the positive electrode current collector is generally aluminum foil.
[0065] In a specific embodiment, the negative electrode active material layer includes: 80-99.8% of negative electrode active material, 0.1-10% of conductive agent, and 0.1-10% of binder. When the components in the negative electrode active material layer are within this range, the negative electrode active material layer has high conductivity and can be adapted to the electrolyte, so that lithium ions can be quickly transmitted in the negative electrode active material layer, thereby improving the cycle performance of the battery. Preferably, the negative electrode active material layer includes: 90-99.6% of negative electrode active material, 0.2-5% of conductive agent, and 0.2-5% of binder.
[0066] The present invention does not limit the selection of the conductive agent and the binder in the negative electrode active material layer. For example, the conductive agent and the binder may be conventional materials in the art, and may be specifically configured as required.
[0067] In a specific embodiment, the positive electrode active material includes at least one of transition metal lithium oxide, lithium iron phosphate, and lithium manganate; the chemical formula of the transition metal lithium oxide is Li 1+x Ni y Co z M (1-y-z) O2, wherein -0.1≤x≤1, 0≤y≤1, 0≤z≤1, and 0≤y+z≤1, and M includes at least one of Mg, Zn, Ga, Ba, Al, Fe, Cr, Sn, V, Mn, Sc, Ti, Nb, Mo, and Zr. When the above positive electrode active material is selected, the positive electrode active material can provide lithium ions for the battery and enable the lithium ions to be quickly transmitted in the battery, which is conducive to achieving high cycle performance of the battery.
[0068] In a specific embodiment, the negative electrode active material includes a carbon-based negative electrode material and / or a silicon-based negative electrode material; the carbon-based negative electrode material includes at least one of artificial graphite, natural graphite, mesophase carbon microspheres, hard carbon, and soft carbon; the silicon-based negative electrode material includes at least one of silicon-oxygen negative electrode material and silicon-carbon negative electrode material. When the negative electrode active material is selected from the above materials, the negative electrode active material has high conductivity, can enable the lithium-ion battery to be quickly deintercalated, and the negative electrode active material has high stability, which is conducive to improving the cycle performance of the battery.
[0069] In a specific embodiment, the conductive agent includes at least one of conductive carbon black, acetylene black, Ketjen black, conductive graphite, conductive carbon fiber, carbon nanotubes, metal powder, and carbon fiber.
[0070] In a specific embodiment, the binder includes at least one of sodium carboxymethyl cellulose, styrene-butadiene latex, polytetrafluoroethylene, and polyethylene oxide.
[0071] In a specific embodiment, the battery further includes a separator, which is a separator known in the art that can be used in batteries and is stable to the electrolyte used, and can be specifically configured as required.
[0072] Hereinafter, the present invention will be further described in detail through specific examples.
[0073] Example 1
[0074] The battery provided in this embodiment is prepared by the following steps:
[0075] 1. Preparation of electrolyte: In a glove box filled with argon (H2O<0.1ppm, O2<0.1ppm), EC / PC / DEC / PP were mixed in a mass ratio of 10 / 20 / 40 / 30, and then 1 mol / L of fully dried lithium hexafluorophosphate (LiPF6) was quickly added thereto, and the compound of formula 2 was added, the mass content B of the compound of formula 2 in the electrolyte was 15000ppm, and stirred evenly. After the water content and free acid test were qualified, the electrolyte was obtained;
[0076] 2. Preparation of negative electrode sheet: The copper foil is subjected to ultrasonic impact treatment at an ultrasonic frequency of 10 to 100 Hz for a time of 10 to 100 s, and the roughness of the copper foil is 0.5 μm; the negative electrode active materials artificial graphite, silicon oxide, sodium carboxymethyl cellulose (CMC-Na), styrene-butadiene rubber, conductive carbon black (SP) and single-walled carbon nanotubes (SWCNTs) are mixed in a mass ratio of 79.5:15:2.5:1.5:1:0.5, deionized water is added, and a negative electrode active slurry is obtained under the action of a vacuum mixer; the negative electrode active slurry is evenly coated on both surfaces of the copper foil; the coated copper foil is dried at room temperature, then transferred to an oven at 80°C for drying for 10 hours, and then cold pressed and cut to obtain a negative electrode sheet; the thickness E of the negative electrode active material layer is 114 μm;
[0077] Among them, the ICP test of the copper foil shows that the silicon content A in the copper foil is 1500ppm;
[0078] 3. Preparation of positive electrode sheet: Mix the positive electrode active materials lithium cobalt oxide (LiCoO2), polyvinylidene fluoride (PVDF), SP (superP) and carbon nanotubes (CNT) in a mass ratio of 96:2:1.5:0.5, add N-methylpyrrolidone (NMP), and stir under the action of a vacuum mixer until the mixed system becomes a positive electrode active slurry with uniform fluidity; evenly coat the positive electrode active slurry on aluminum foil, dry the coated aluminum foil, and then roll and cut to obtain the desired positive electrode sheet; the thickness D of the positive electrode active material layer is 90 μm;
[0079] 4. Preparation of the battery: stack the positive electrode sheet, the negative electrode sheet and the separator in the order of the positive electrode sheet, the separator and the negative electrode sheet, and then wind them to obtain a battery core; place the battery core in an outer packaging aluminum foil, inject the electrolyte into the outer packaging, and obtain the battery through vacuum packaging, standing, forming, shaping, sorting and other processes. The charge and discharge range of the battery of the present invention is 3.0-4.5V.
[0080] Example 2
[0081] The preparation method of the battery of this embodiment is substantially the same as that of the embodiment 1, except that the mass content A of silicon element in the copper foil is 2000 ppm.
[0082] Example 3
[0083] The preparation method of the battery of this embodiment is substantially the same as that of the embodiment 1, except that the mass content A of silicon element in the copper foil is 700 ppm.
[0084] Example 4
[0085] The preparation method of the battery of this embodiment is substantially the same as that of the embodiment 1, except that the mass content A of silicon element in the copper foil is 2500 ppm.
[0086] Example 5
[0087] The preparation method of the battery of this embodiment is substantially the same as that of the embodiment 1, except that the mass content A of silicon element in the copper foil is 600 ppm.
[0088] Example 6
[0089] The preparation method of the battery of this embodiment is substantially the same as that of embodiment 1, except that the mass content B of the compound of formula 2 in the electrolyte is 25000 ppm.
[0090] Example 7
[0091] The preparation method of the battery of this embodiment is substantially the same as that of embodiment 1, except that the mass content B of the compound of formula 2 in the electrolyte is 50000 ppm.
[0092] Example 8
[0093] The preparation method of the battery of this embodiment is substantially the same as that of embodiment 1, except that the mass content B of the compound of formula 2 in the electrolyte is 1000 ppm.
[0094] Example 9
[0095] The preparation method of the battery of this embodiment is substantially the same as that of embodiment 1, except that the mass content B of the compound of formula 2 in the electrolyte is 55000 ppm.
[0096] Example 10
[0097] The preparation method of the battery of this embodiment is substantially the same as that of embodiment 1, except that the mass content B of the compound of formula 2 in the electrolyte is 900 ppm.
[0098] Embodiment 11
[0099] The preparation method of the battery in this embodiment is substantially the same as that in embodiment 1, except that the roughness of the copper foil is 1 μm.
[0100] Example 12
[0101] The preparation method of the battery in this embodiment is substantially the same as that in Embodiment 1, except that the copper foil is not subjected to ultrasonic impact treatment, and the roughness of the copper foil is 0.
[0102] Embodiment 13
[0103] The preparation method of the battery of this embodiment is substantially the same as that of the embodiment 1, except that the roughness of the copper foil is 1.1 μm.
[0104] Embodiment 14
[0105] The preparation method of the battery of this embodiment is substantially the same as that of Embodiment 1, except that the compound of Formula 2 is replaced by the compound of Formula 3.
[0106] Embodiment 15
[0107] The preparation method of the battery of this embodiment is substantially the same as that of Embodiment 1, except that the compound of Formula 2 is replaced by the compound of Formula 7.
[0108] Example 16
[0109] The preparation method of the battery of this embodiment is substantially the same as that of Embodiment 1, except that the compound of Formula 2 is replaced by the compound of Formula 11.
[0110] Embodiment 17
[0111] The preparation method of the battery of this embodiment is substantially the same as that of Embodiment 1, except that the compound of Formula 2 is replaced by the compound of Formula 12.
[0112] Embodiment 18
[0113] The preparation method of the battery of this embodiment is substantially the same as that of Embodiment 1, except that the compound of Formula 2 is replaced by the compound of Formula 17.
[0114] Embodiment 19
[0115] The preparation method of the battery of this embodiment is substantially the same as that of Embodiment 1, except that the electrolyte further includes the compound represented by Formula 21, and the mass percentage of the compound represented by Formula 21 in the electrolyte is 0.01%.
[0116] Embodiment 20
[0117] The preparation method of the battery of this embodiment is substantially the same as that of Embodiment 19, except that the mass percentage content F of the compound of Formula 21 in the electrolyte is 0.03%.
[0118] Embodiment 21
[0119] The preparation method of the battery of this embodiment is substantially the same as that of Embodiment 19, except that the mass percentage content F of the compound of Formula 21 in the electrolyte is 0.05%.
[0120] Embodiment 22
[0121] The preparation method of the battery of this embodiment is substantially the same as that of Embodiment 19, except that the mass percentage content F of the compound of Formula 21 in the electrolyte is 0.06%.
[0122] Embodiment 23
[0123] The preparation method of the battery of this embodiment is substantially the same as that of the embodiment 2, except that the thickness D of the positive electrode active material layer is 80 μm.
[0124] Embodiment 24
[0125] The preparation method of the battery of this embodiment is substantially the same as that of the embodiment 2, except that the thickness E of the negative electrode active material layer is 180 μm.
[0126] Comparative Example 1
[0127] The preparation method of the battery of this comparative example is substantially the same as that of Example 20, except that the compound of formula 2 is not added to the electrolyte.
[0128] Comparative Example 2
[0129] The preparation method of the battery of this comparative example is substantially the same as that of Example 20, except that succinonitrile replaces the compound of formula 2.
[0130] Comparative Example 3
[0131] The preparation method of the battery of this comparative example is substantially the same as that of Example 20, except that the copper foil does not contain Si.
[0132] Table 1
[0133]
[0134]
[0135] Test example
[0136] The internal resistance test of the batteries of the embodiment and the comparative example was performed: a multimeter was used to test the positive and negative electrodes of the batteries and test the internal resistance of the batteries. The results are shown in Table 2.
[0137] Battery internal resistance test:
[0138] Safety performance test: An extrusion test and an impact test were used. The batteries of the comparative example and the embodiment were squeezed for 1 min at 4.5V using a 1MPa pressure battery to observe whether they caught fire or exploded. A total of 10 batteries were tested. The results are shown in Table 2.
[0139] Cycle performance test: The batteries of the comparative example and the embodiment were charged and discharged for 400 cycles at 25°C at a rate of 1C; at the same time, the capacity of the 100th week was divided by the capacity of the 1st week to obtain the cycle capacity retention rate. The results are shown in Table 2.
[0140] Low temperature cycle test: The batteries of the comparative example and the embodiment were charged and discharged for 300 cycles at 0°C at a rate of 0.2C; at the same time, the capacity of the 100th week was divided by the capacity of the 1st week to obtain the cycle capacity retention rate. The results are shown in Table 2.
[0141] High temperature cycle test: The batteries of the comparative example and the embodiment were charged and discharged for 300 cycles at 55°C at a rate of 1C; at the same time, the capacity of the 100th week was divided by the capacity of the 1st week to obtain the cycle capacity retention rate. The results are shown in Table 2.
[0142] Table 2
[0143]
[0144]
[0145] It can be seen from Table 2 that, according to the comparison between Example 1 and Comparative Examples 1-3, only when the copper foil contains silicon and the electrolyte contains ether nitrile compounds, the silicon in the copper foil can catalyze the ether nitrile compounds to form a passivation film on the surface of the copper foil, thereby preventing acidic substances such as PF5, POF3, HF in the electrolyte from corroding the copper foil, avoiding the formation of copper dendrites, and preventing copper dendrites from piercing the copper foil and causing a battery short circuit, thereby improving the safety performance of the battery.
[0146] According to the comparison of Examples 1-5, it can be seen that when the mass content of silicon in the copper foil is in the range of 700-2000 ppm, the stability, safety performance and cycle performance of the battery can be improved.
[0147] According to the comparison of Examples 1 and 6-10, when the mass content B of the compound of Formula 1 in the electrolyte is in the range of 1000-50000 ppm, the safety performance and cycle performance of the battery can be improved.
[0148] According to the comparison between Examples 1 and 11-13, it can be seen that when the roughness of the copper foil is ≤1 μm, the safety performance of the battery can be improved.
[0149] According to Examples 1 and 14-18, when the compound of Formula 1 is selected from the above compounds, the safety performance of the battery can be improved.
[0150] According to the comparison between Examples 1 and 19-22, when the mass percentage F of the compound of Formula 21 in the electrolyte satisfies: 0.01%≤F≤0.05%, the safety performance and cycle performance of the battery can be further improved.
[0151] According to the comparison between Examples 1 and 23, when the thickness of the positive electrode active material layer is in the range of 20-130 μm, the high temperature performance, safety performance and low temperature performance of the battery can be improved.
[0152] According to the comparison between Examples 1 and 24, when the thickness of the negative electrode active layer is in the range of 30-180 μm, the cycle performance of the battery can be improved.
[0153] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A battery, characterized in that: It includes a positive electrode sheet, a negative electrode sheet and an electrolyte, wherein the negative electrode sheet includes a negative electrode current collector, the negative electrode current collector includes a copper foil, and the copper foil includes silicon element; The electrolyte includes an ether nitrile compound.
2. The battery according to claim 1, characterized in that The ether nitrile compound includes a compound shown in Formula 1: Wherein, R is selected from substituted or unsubstituted C1-C30 alkyl, and the substituent of R includes C1-C10 alkoxy, cyano, -O-(CH2) m -At least one of CN; n is selected from an integer between 0 and 5, and m is selected from an integer between 1 and 8; Preferably, R is selected from substituted or unsubstituted C1-C20 alkyl, and the substituents of R include C1-C5 alkoxy, cyano, -O-(CH2) m -At least one of CN; n is selected from 0, 1, 2, and m is selected from an integer from 1-5.
3. The battery according to claim 1 or 2, characterized in that: The compound represented by Formula 1 includes at least one of the compounds represented by Formula 2 to Formula 20:
4. The battery according to claim 1 or 2, characterized in that: The mass content of the silicon element in the copper foil is 700-2000 ppm; and / or the mass content of the compound represented by Formula 1 in the electrolyte is 1000-50000 ppm.
5. The battery according to claim 4, characterized in that The positive electrode sheet in the battery comprises a positive electrode active material layer, and the thickness of the positive electrode active material layer is 20-130 μm.
6. The battery according to any one of claims 1 to 5, characterized in that: The roughness of the copper foil is ≤1 μm.
7. The battery according to any one of claims 1 to 6, characterized in that: The electrolyte also includes a compound shown in Formula 21:
8. The battery according to claim 7, characterized in that The mass percentage F of the compound represented by formula 21 in the electrolyte satisfies: 0.01%≤F≤0.05%.
9. The battery according to claim 8, characterized in that The negative electrode comprises a negative electrode active material layer, and the thickness of the negative electrode active material layer is 30-180 μm.
10. The battery according to any one of claims 1 to 9, characterized in that: The positive electrode includes a positive electrode active material, wherein the positive electrode active material includes a transition metal lithium oxide, and the chemical formula of the transition metal lithium oxide is Li 1+ x Ni y Co z M (1-y-z) O2, wherein -0.1≤x≤1, 0≤y≤1, 0≤z≤1, and 0≤y+z≤1, and M includes at least one of Mg, Zn, Ga, Ba, Al, Fe, Cr, Sn, V, Mn, Sc, Ti, Nb, Mo, and Zr; And / or, the negative electrode active material includes a silicon-based negative electrode material, and the silicon-based negative electrode material includes at least one of a silicon-oxygen negative electrode material and a silicon-carbon negative electrode material.